Confirmatory factor analysis of the multicultural anger expression and hostility inventory - Moscoso, Manolete S. (2016)
The main purpose of this study was to verify the factorial structure of the two scales that make up the Multicultural Inventory of Expression of Anger and Hostility from a confirmatory perspective. We performed the Confirmatory Factor Analysis with a non-probability sample of 264 participants from a private university in Lima, Peru. The sampling included university students (25%), faculty members (17.8%) and administrative staff (57.2%). The reliability of the instrument was evaluated using the congeneric, tau-equivalent and parallel models for each of the six subscales of the instrument, as well as calculated based on Cronbach's alpha coefficient with confidence intervals. Results: Factor analysis performed in the present Peruvian sample identified four dimensions for the Anger Expression Scale (Anger-In, Anger-Out, Anger/Control In, and Anger/Control-Out) and two factors for the Hostility Scale (impulsive reaction to anger; and temperament), which substantially verified the factor structure of previous studies conducted in Latin American samples. The congeneric modelindicates an appropriate fit for each of the subscales of anger and hostility. Based on the results of the Confirmatory Factor Analysis performed in the present study, the factorial structure of both scales of the Multicultural Anger Expression and Hostility Inventory is robust and shows substantial empirical evidence of construction validity and internal consistency of the instrument. DOI: https://doi.org/10.24265/liberabit.2016.v22n2.02